Redesign of Positive Fictitious Efforts After the Job Creation Law : Redesain Upaya Fiktif Positif Pasca Undang-Undang Cipta Kerja - Zaka Firma Aditya; Sholahuddin Al-Fatih (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
The Job Creation Law has not only changed positive-fictitious construction from ten to five days, but also abolished the administration court authority in deciding positive-fictitious applications. Naturally, every administrative action can be sued by the public to court with the aim that these actions follow legal rules and human rights values. Thus, the administrative court authority in deciding positive-fictitious applications is a control mechanism so that there is no abuse of authority from government. This article discuss: 1) the legal-historical and dynamics of positive-fictitious decisions; 2) the implications of positive-fictitious arrangements in job creation law, and 3) the redesign of positive-fictitious efforts after job creation law. The results of this research indicate that after the Job Creation Law, it is necessary to review the positive-fictitious decisions, especially by paying attention to the institution authorized to decide on fictitious applications, the use of AI applications, and the time of fictitious submissions.